The effect of devolution on health: a generalised synthetic control analysis of Greater Manchester, England. (October 2022) - Britteon, Philip; Fatimah, Alfariany; Lau, Yiu-Shing; Anselmi, Laura; Turner, Alex J; Gillibrand, Stephanie; Wilson, Paul; Checkland, Kath; Sutton, Matt
Summary: Background: The devolution of public services from central to local government can increase sensitivity to local population needs but might also reduce the expertise and resources available. Little evidence is available on the impact of devolution on population health. We evaluated the effect of devolution affecting health services and wider determinants of health on life expectancy in Greater Manchester, England. Methods: We estimated changes in life expectancy in Greater Manchester relative to a control group from the rest of England (excluding London), using a generalised synthetic control method. Using local district-level data collected between Jan 1, 2006 and Dec 31, 2019, we estimated the effect of devolution on the whole population and stratified by sex, district, income deprivation, and baseline life expectancy. Findings: After devolution, from November, 2014, life expectancy in Greater Manchester was 0·196 years (95% CI 0·182–0·210) higher than expected when compared with the synthetic control group with similar pre-devolution trends. Life expectancy was protected from the decline observed in comparable areas in the 2 years after devolution and increased in the longer term. Increases in life expectancy were observed in eight of ten local authorities, were larger among men than women (0·338 years [0·315–0·362] for men; 0·057 years [0·040–0·074] for women), and were larger in areas with high income deprivation (0·390 years [0·369–0·412]) and lower life expectancy before devolution (0·291 years [0·271–0·311]). Interpretation: Greater Manchester had better life expectancy than expected after devolution. The benefits of devolution were apparent in the areas with the highest income deprivation and lowest life expectancy, suggesting a narrowing of inequalities. Improvements were likely to be due to a coordinated devolution across sectors, affecting wider determinants of health and the organisation of care services. Funding: The Health Foundation and the National Institute for Health and Care Research.